Exploring the Three C’s: Calm, Concentration, and Cold in ‘Nordic’ Leadership Practice - Janning, Finn (Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This paper explores how calm, concentration, and coldness shape a vulnerable leadership style, fostering trust, psychological safety, and flexibility. Drawing from Nordic leadership traditions, the paper examines how these traits enhance emotional resilience and openness. Background Problems: Contemporary leadership often misunderstands vulnerability, despite its potential to enhance trust and psychological safety. The gap lies in understanding how specific qualities like calm, concentration, and coldness contribute to psychological flexibility. Novelty: Shows how traits often seen as passive or negative—coldness, calmness, and concentration can foster psychological flexibility and trust. It offers a new perspective on how Nordic leadership balances vulnerability and resilience. Research Methods: Using a phenomenological approach, a personal anecdote is interpreted through leadership theories and psychological framework. Finding/Results: The paper proposes that calmness, concentration, and coldness enhance leaders' psychological flexibility, fostering trust and improving team dynamics. Conclusion: These traits are essential for trust-based, adaptive leadership that balances vulnerability and resilience, benefiting organizational psychological safety and flexibility.